Effects of physical activity on the severity of illness and mortality in COVID-19 patients: A systematic review and meta-analysis - Sittichai, Nuttawut; Parasin, Nichapa; Saokaew, Surasak; Kanchanasurakit, Sukrit; Kayod, Nuttawan; Praikaew, Ketnapa; Phisalprapa, Pochamana; Prasannarong, Mujalin (Frontiers in Physiology, 2022)
Purpose: This systematic review and meta-analysis investigated the association between Physical activity (PA) before Coronavirus Disease 2019 (COVID-19) infection and the severity of illness and mortality in COVID-19 patients. Methods: A comprehensive search was undertaken to identify retrospective and nonrandomized controlled trial studies comparing the severity and mortality of COVID-19 infection among COVID-19 patients who had previously reported their participation in PA with those who had not. The databases searched were PubMed, Cochrane Library, Scopus, Science Direct, EMBASE, OPENGREY.EU, and ClinicalTrials.gov. The risk of bias was assessed using the Newcastle-Ottawa Scale. A random-effects model was used for determining pairwise meta-analyses. The protocol was registered with PROSPERO (CRD42021262548). Results: Eighteen studies met the inclusion criteria (5 cross-sectional, 12 cohort, and 1 case-control studies). All 1 618 680 subjects were adults. PA significantly decreased the risk of death in COVID-19 patients (odds ratio [OR] 0.34; 95% confidence interval [CI], 0.19–0.62; p < 0.001) and the risk of severe outcomes (OR 0.60; 95% CI, 0.48–0.76; p < 0.001). Subgroup analysis showed that PA for ≥150 min/wk at a moderate intensity or ≥75 min/wk at a vigorous intensity reduced the risks of severity and mortality. Vigorous PA reduced mortality risk, whereas moderate to vigorous PA reduced the risks of severity and mortality. Conclusion: PA before infection might reduce severity and mortality in COVID-19 patients, especially PA ≥ 150 min/wk of moderate activity or ≥75 min/wk of vigorous activity. However, careful interpretations should be considered due to the difference in PA patterns and severity definitions among included studies. This finding implies that engaging in regular PA, even in different patterns, has beneficial effects on the severity and mortality of COVID-19 patients.